Unpublished documents: the correspondence between King Mihai and democracy activist Ion Rațiu between 1980–1990 - Bianca Pădurean (Dialogica: Revistă de Studii Culturale și Literatură)
King Mihai and Ion Rațiu corresponded extensively in the 1980s–1990s and later. Some of these letters are kept in the Archives of the Romanian Cultural Center in London, in Manchester Square (owned by the Rațiu family). These letters bear witness to the work of both King Mihai and Ion Rațiu for the benefit of Romanians abroad. The correspondence that is the subject of this article deals with subjects such as King Mihai’s interview with Hungarian Television, testimonies about the “Danish branch”, the way in which thousands of Romanians managed to escape from the communist camp or simply personal topics. The article is supplemented by previously unpublished notes from Ion Rațiu’s diary (his diaries with his notes up to 1973 are now published), which add to the subject. These letters and notes are evidence of the intense public and private activity of the two protagonists, King Mihai and Ion Rațiu, in a turbulent decade of history, which ended with great regime changes in Europe. Among these letters there is also the correspondence between Ion Rațiu and Queen Ana, relevant in the context of the rescue of the “Danish filiere”, to which the Queen contributed.